2000
DOI: 10.1093/carcin/21.7.1391
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic rats carrying copies of the human c-Ha- ras proto-oncogene exhibit enhanced susceptibility to N -butyl- N -(4-hydroxybutyl)nitrosamine bladder carcinogenesis

Abstract: We have established a transgenic rat line carrying three copies of the human c-Ha-ras proto-oncogene with its own original promoter region, Jcl/SD-TgN(HrasGen)128Ncc (Hras128) rat. c-Ha-ras protein from expression of transduced and endogenous c-Ha-ras genes could be detected in the bladder epithelium of untreated transgenic rats. To examine their susceptibility to N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN)-induced urinary bladder carcinogenesis, male transgenic and wild-type littermates were treated with 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…1) Similarly, the transgene mutation rate in urinary bladder lesions induced by another nitrosamine, N-butyl-N-(4-hydroxybutyl)nitrosamine, was not predominant. 37) In contrast, the mutated band densities observed in esophageal tumors in the current study indicated the tumors to contain cells with mutated transgene as the major population (Fig. 1).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…1) Similarly, the transgene mutation rate in urinary bladder lesions induced by another nitrosamine, N-butyl-N-(4-hydroxybutyl)nitrosamine, was not predominant. 37) In contrast, the mutated band densities observed in esophageal tumors in the current study indicated the tumors to contain cells with mutated transgene as the major population (Fig. 1).…”
Section: Discussioncontrasting
confidence: 64%
“…[26][27][28] In contrast, mutations in the c-Ha-ras gene are rare in bladder or liver tumors induced by carcinogens in rats. [34][35][36] We have found that our Hras128 strain is highly susceptible to MNU-induced mammary, 9) N-butyl-N-(4-hydroxybutyl)nitrosamine-induced urinary bladder 37) and, in the present work, NMBA-induced esophageal carcinogenesis. The results indicate that mutations of c-Ha-ras can play important roles in neoplasia in the esophagus, in contrast to the breast and urinary bladder.…”
Section: Discussionmentioning
confidence: 51%
“…Human c-Ha-ras proto-oncogene Tg and non-Tg rats I 5 To whom correspondence should be addressed. E-mail: htsuda@med.nagoya-cu.ac.jp bred by CLEA Japan Inc., Tokyo 32,34) at 7 weeks of age were maintained in plastic cages in an air conditioned room at 22±2°C and 55±10% humidity. The animals were all allowed free access to pellet basal diet (Oriental Yeast Co., Ltd., Tokyo), from which soy constituents, isoflavones which were known to act as estrogens, had been eliminated (Table 1), and to tap water.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the tumor cells contained mutated transgene, but not endogenous Hras gene, indicating that activation of the transgene plays an important role in such rapid development of tumors. The animals have also been found to be susceptible to N-butyl-N-(4-hydroxybutyl)nitrosamine urinary bladder, 34) N-nitrosomethylbenzylamine esophageal, 35) and DMBA skin carcinogenesis. 36) We recently showed that the transgenic (Tg) rats have a potential for use in medium-term bioassay models to test for the modifying effects of estrogenic environmental compounds on mammary tumor development.…”
mentioning
confidence: 99%
“…7) In humans, Ki-ras mutations are preferentially found in colon, 8,9) pancreatic duct 10) and bile duct carcinomas, 11) and N-ras mutations are typically seen in myeloid leukemia. 12) We have generated a transgenic rat line, harboring copies of a human c-Ha-ras proto-oncogene (Hras128 rat), and have shown that these animals are highly susceptible to mammary, 13,14) bladder 15) and esophageal 16) carcinogens.…”
mentioning
confidence: 99%